2012
DOI: 10.2224/sbp.2012.40.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Brands and consumer behavior

Abstract: In this research, on the basis of a review of the literature on brand image, brand equity, involvement, and purchase intention, we developed a questionnaire to explore the correlation of brand image and brand equity with consumer purchase intention. Respondents were university students in Taiwan. After analysis with SPSS, the following results were found: brand image significantly affected brand equity, brand equity significantly affected purchase intention, and brand image significantly affected purchase inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…Weak support was found for the perceived quality and brand awareness dimensions. Further, Chen et al (2012) reported significant positive association between brand image and brand equity among Taiwanese students. Similarly, Buil et al (2013) underscored significant positive effect of brand image and perceived quality on overall brand equity.…”
Section: Brand Equity and Its Dimensionsmentioning
confidence: 88%
“…Weak support was found for the perceived quality and brand awareness dimensions. Further, Chen et al (2012) reported significant positive association between brand image and brand equity among Taiwanese students. Similarly, Buil et al (2013) underscored significant positive effect of brand image and perceived quality on overall brand equity.…”
Section: Brand Equity and Its Dimensionsmentioning
confidence: 88%
“…Clear intention plays an important role in human actions, however, some studies has revealed that there are difficulties in translating intentions and actual behavior (Ajzen, 2001). Therefore, purchase intention is seen as an important concept and widely used to predict the behavior of the actual purchase (Armstrong et al, 2000;Chen et al, 2012;Qing et al, 2012). We hypothesize:…”
Section: Intention and Actual Purchasementioning
confidence: 99%
“…Clear intention plays an important role to human actions, however, some studies have revealed that there were difficulties in translating intentions and actual behavior (Ajzen, 2001). Therefore, purchase intention is seen as an important concept and widely used to predict the behavior of the actual purchase (Armstrong et al, 2000;Chen et al, 2012;Qing et al, 2012;Tsiotsou, 2006).…”
Section: Perceived Riskmentioning
confidence: 99%